MANAGEMENT CONSIDERATIONS IN THE CONTEXT OF MULTIPLE OBSTETRIC COMORBIDITIES - A CASE REPORT (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Obstetric comorbidities significantly increase the risk of adverse obstetric outcomesbecause of their association with complications that can occur suddenly and escalate rapidly.Case presentation: A morbidly obese 26-year-old primigravida initially presented with first-trimesterbleeding. She consistently declined monitoring and was not adherent to the multidisciplinary treatmentplans despite serial counseling. This state persisted even when she was diagnosed with gestationaldiabetes mellitus and preeclampsia. She incurred gross fetal macrosomia and was admitted at term forinduction of labor. By the third prostaglandin, there was overt fetal tachycardia that necessitated anemergency cesarean delivery. Failed spinal anesthesia necessitated generalization. Access wasimpeded by a massive panniculus, necessitating tape retraction to reveal the surgical site. A distressedapneic baby was delivered, after which she developed an atonic uterus that necessitated uterine bracesuturing and intramyometrial PGF2α. The baby underwent therapeutic hypothermia. Postoperatively, shewas monitored and underwent repeated counseling.Discussion: This patient was noncompliant to medication and monitoring, she had multiple interactingcomorbidities, and she ended up having an avoidable multiple near-miss. There is a need to develop anobstetric comorbidity scoring index and validate it locally.Conclusion: If guided by a logical algorithmic sequence of guided responses, the development andapplication of a local risk and comorbidity scoring index may substantively reduce the risk of adverseobstetric outcomes. This is vital if sustainable development goals are to be realized.